Evaluation of Vimentin-Positive Circulating Tumor Cells in Breast Cancer and Their Association with Pre and Post-chemotherapy - Yulian, Erwin Danil; Utami, Sri Anidyo; Wulandari, Dewi; Kekalih, Aria; Idhil, Andi Nurul Isri Indriany (http://dharmais.co.id/, 2026)
Background: Breast cancer is the most common cancer among women worldwide, leading to 670,000 deaths globally in 2022. Epithelial-mesenchymal transition (EMT) plays a role in the metastasis of breast cancer. The EMT process begins with the invasion of cancer cells into surrounding tissues, intravasation into blood vessels, circulating tumor cells (CTCs), evasion of the immune process, and extravasation to a new location. Epithelial cells undergoing EMT are characterized by an increase in mesenchymal markers such as vimentin, which indicates migration of breast cancer cells. Previous studies have shown that EMT contributes to resistance to chemotherapy. This study aims to evaluate pre and post-chemotherapy of vimentin-positive CTCs in breast cancer patients and the association with chemotherapy. Methods: A prospective cohort study at Dr. Cipto Mangunkusumo General Hospital and Koja Hospital, Jakarta, from March to June 2024. This study obtained vimentin-positive CTCs pre- and post-chemotherapy and clinicopathological factors in 24 breast cancer patients. The inclusion criteria were patients diagnosed with breast cancer with histological subtype invasive carcinoma of no special type, and patients were eligible for chemotherapy and continued to receive first-line chemotherapy. Vimentin-positive CTCs were evaluated by using the FITC immunofluorescence technique with a BD FACSLyric flow cytometer. The association between the vimentin-positive CTCs pre- and post-chemotherapy was analysed by using the Wilcoxon test. The Mann-Whitney test was used to analyse the association between the delta number of vimentin CTCs and clinicopathological factorsResults: Total vimentin CTCs pre- and post-chemotherapy were measured in 24 patients. The delta vimentin-positive CTCs were calculated as the difference between total vimentin-positive CTCs pre-chemotherapy minus total CTCs post-chemotherapy. A significant association was observed between the vimentin-positive CTC levels pre- and post-chemotherapy (p = 0.009). Clinicopathological factor analysis showed no significant association between delta CTCs. Conclusions: The vimentin-positive CTC level in breast cancer patients was significantly reduced post received chemotherapy. Due to the small sample size, this study may have limited statistical power. This study suggests further research on vimentin-positive CTCs as predictor factors for chemotherapy response in breast cancer patients.